Enhancing real-time CAN communications by the prioritization of urgent messages at the outgoing queue - António J. Pires (2006)
To ensure the correct behaviour of a Networked Control System, the communication network must provide a reliable and timely communication service. The two components with the highest impact on the communication delays are the Medium Access Control (MAC) protocol and the local communication stack, therefore, the usage of an adequate communication stack is of utmost importance to guarantee the timing correctness of a feedback control application. In this paper, we propose the use of state-of-the-art scheduling algorithms to manage the outgoing queue of a local communication stack. We demonstrate that it is possible to improve the responsiveness of applications supported by the CAN communication protocol, by using just a light scheduling middleware to adequately schedule the outgoing queue. We also show that implementing such middleware even on top of COTS communication hardware, opens the possibility to enhance the communication process by minimizing the number of deadline misses for highly loaded network scenarios.